The reconstruction of a dorsal digital defect using a reverse homodigital island flap incorporating vascularized tendon - Tonkin, M.A.; Ahmad, T.S. (Elsevier, 1997)
We describe a modification of the reverse homodigital island flap, in which a segment of lateral band of the extensor apparatus is harvested with the flap and used to reconstruct the extensor insertion to the distal phalanx.